Proliferative ability of circulating tumor cells is a prognostic factor in Early-Stage lung adenocarcinoma. (April 2023) - Che, Ting-Fang; Chiu, Chao-Hua; Wu, Yu-Chung; Chen, Jia-Yang; Chou, Teh-Ying; Cheng, Yi-Chun; Chiang, Chi-Lu; Huang, Chien-Sheng; Tuang, I-Shuan; Ho, Yang-Hui; Hong, Jian-Hua; Huang, Yen-Jang; et al.
Highlights: Our microfluidic DS platform has a high detection rate and cultivation capability for clinical LUAD patients. Cultured CTC count and proliferative ability is highly associated with metastasis and cancer prognosis in LUAD patients. Cultured CTC count is suggested as a prognostic factor in early-stage LUAD patients. Abstract: Introduction: Circulating tumor cells (CTCs) and their proliferative ability in lung adenocarcinoma (LUAD) were not well-investigated. We developed a protocol combining an efficient viable CTC isolation and in-vitro cultivation for the CTC enumeration and proliferation to evaluate their clinical significance. Method: The peripheral blood of 124 treatment-naïve LUAD patients were processed by a CTC isolation microfluidics, DS platform, followed by in-vitro cultivation. LUAD-specific CTCs were defined by immunostaining of DAPI+/CD45-/(TTF1/CK7)+ and were enumerated upon isolation and after 7-day cultivation. The CTC proliferative ability was evaluated by both the cultured number and the culture index, a ratio of cultured CTC number to the initial CTC number in 2 mL of blood. Result: All but two LUAD patients (98.4%) were detected with at least one CTC per 2 mL of blood. Initial CTC numbers did not correlate with metastasis (75 ± 126 for non-metastatic, 87 ± 113 for metastatic groups; P  = 0.203). In contrast, both the cultured CTC number (mean: 28, 104, and 185 in stage 0/I, II/III, and IV; P  < 0.001), and the culture index (mean: 1.1, 1.7 and 9.3 in stage 0/I, II/III, and IV; P  = 0.043) were significantly correlated with the stages. Overall survival analysis within the non-metastatic group (N = 53) showed poor prognosis for patients with elevated cultured counts (cutoff ≥ 30; P  = 0.027). Conclusion: We implemented a CTC assay in clinical LUAD patients with a high detection rate and cultivation capability. Cultured CTC count and proliferative ability, rather than the crude CTC numbers, highly associated with cancer prognosis.